Mission For Life the story of the family of Adoniram Judson, the dramatic events of the first American foreign mission, and the course of evangelical religion in the nineteenth century - Brumberg, Joan Jacobs (New York Free Press, 1980)
Adoniram Judson (1788-1850) was born at Malden and reared at Plymouth, Massachusetts, and was the first American to become a fully committed evangelical foreign missionary, first for the Congregationalists in 1812, but almost immediately for the America
Keywords: Judson family. Judson. Boardman